2016
DOI: 10.1002/brb3.603
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prophylactic treatment and long‐term prognosis after TIA and different subtypes of stroke. A 25‐year follow‐up hospital‐based observational study

Abstract: ObjectivesTo assess long‐term prognosis after transient ischemic attack (TIA)/subtypes of stroke relative to secondary prophylactic treatment(s) given.Materials and MethodsRetro/prospective follow‐up of patients hospitalized in the Stroke Unit or in the Department of Neurology, Linköping, in 1986 and followed up to Feb. 2011.ResultsA total of 288 men were followed up for 2254 years (mean 7.8 years) and 261 women for 1984 years (mean 7.6 years). In men, the distribution to anticoagulants (AC) (warfarin treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
2
4
0
Order By: Relevance
“…In our analysis, a higher DBP at baseline and antiplatelet treatment were independent predictors for survival. This nding was coherent with the Sweden study that antiplatelet therapy in patients with ischemic stroke had a survival bene t [24]. Lowering BP after stroke is associated with a signi cant decrease in stroke recurrence, but the optimal target of BP for ischemic stroke patient is uncertain.…”
Section: Discussionsupporting
confidence: 66%
“…In our analysis, a higher DBP at baseline and antiplatelet treatment were independent predictors for survival. This nding was coherent with the Sweden study that antiplatelet therapy in patients with ischemic stroke had a survival bene t [24]. Lowering BP after stroke is associated with a signi cant decrease in stroke recurrence, but the optimal target of BP for ischemic stroke patient is uncertain.…”
Section: Discussionsupporting
confidence: 66%
“…As in the previous study that did not include TC/TG levels in Cox regression analysis to assess predictors of death [24], this study also supports treatment of high systolic blood pressure, fasting blood glucose ≥6.1 mmol/L or history of diabetes, both in primary and secondary prevention, and administration of antithrombotic/antiplatelet therapy as secondary prophylaxis with no contraindications.…”
Section: Sex Men Womensupporting
confidence: 73%
“…This study included patients with TIA/stroke hospitalized in 1986 at the Stroke unit or Department of Neurology and who had a fasting lipid analysis performed at admission. All patients were followed up until February 2011 [24]. TIA was defined as an acute onset of focal neurological symptom(s) and sign(s) or retinal that had been transient within 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Of 577 potentially eligible records identified for the systematic review, we identified 28 eligible articles reporting on 23 studies 2 , 3 , 4 , 5 , 9 , 17 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 (9 trials and 14 observational studies) including 4889 patients with cryptogenic TIA/stroke and PFO who were receiving medical treatment alone (eFigure 1 in the Supplement ). Noneligible studies included observational studies 39 , 40 , 41 , 42 , 43 , 44 and 1 randomized clinical trial (47 patients with cryptogenic stroke/TIA randomized to either warfarin or aspirin) 45 with a population below the threshold for inclusion (<100 patients with cryptogenic TIA/stroke enrolled); observational studies on an unsuitable population (mostly retrospective studies selecting patients on the basis of echocardiographic finding of a PFO, where the analysis included patients without stroke, or patients with both cryptogenic and noncryptogenic TIA/stroke) 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ; secondary publications of an included study 55 , 56 ; and a study that reported only composite outcomes of TIA/stroke and peripheral embolism. 57 We contacted 8 authors and obtained unpublished data from 4 individuals.…”
Section: Resultsmentioning
confidence: 99%